Unraveling the genetic architecture of copy number variants associated with schizophrenia and other neuropsychiatric disorders. Issue 5 (8th November 2016) - Rutkowski, Timothy P.; Schroeder, Jason P.; Gafford, Georgette M.; Warren, Stephen T.; Weinshenker, David; Caspary, Tamara; Mulle, Jennifer G.
Abstract : Recent studies show that the complex genetic architecture of schizophrenia (SZ) is driven in part by polygenic components, or the cumulative effect of variants of small effect in many genes, as well as rare single‐locus variants with large effect sizes. Here we discuss genetic aberrations known as copy number variants (CNVs), which fall in the latter category and are associated with a high risk for SZ and other neuropsychiatric disorders. We briefly review recurrent CNVs associated with SZ, and then highlight one CNV in particular, a recurrent 1.6‐Mb deletion on chromosome 3q29, which is estimated to confer a 40‐fold increased risk for SZ. Additionally, we describe the use of genetic mouse models, behavioral tools, and patient‐derived induced pluripotent stem cells as a means to study CNVs in the hope of gaining mechanistic insight into their respective disorders. Taken together, the genomic data connecting CNVs with a multitude of human neuropsychiatric disease, our current technical ability to model such chromosomal anomalies in mouse, and the existence of precise behavioral measures of endophenotypes argue that the time is ripe for systematic dissection of the genetic mechanisms underlying such disease. © 2016 Wiley Periodicals, Inc.